2021
DOI: 10.1007/s12035-021-02509-4
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Can Attenuate Astrocyte Activation to Treat Spinal Cord Injury by Inhibiting Inflammatory Responses

Abstract: Several preclinical and clinical studies have attempted to elucidate the pathophysiological mechanism associated with spinal cord injury. However, investigations have been unable to define the precise related mechanisms, and this has led to the lack of effective therapeutic agents for the condition. Neuroinflammation is one of the predominant processes that hinder spinal cord injury recovery. Resveratrol is a compound that has several biological features, such as antioxidation, antibacterial, and antiinflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 114 publications
0
10
0
Order By: Relevance
“…Resveratrol (Res), as a potential SCI therapeutic drug, exhibits a variety of pharmacological effects, such as good antioxidant, anti-inflammatory, neuroprotective, and antiapoptotic properties (Fu et al, 2018 ; Huang et al, 2019 ; Fan et al, 2021 ). However, due to its poor water solubility, low bioavailability, and difficulty in crossing physiological barriers to reach the injury site, its application in SCI is limited greatly (Zhang et al, 2014 ; Miguel et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Resveratrol (Res), as a potential SCI therapeutic drug, exhibits a variety of pharmacological effects, such as good antioxidant, anti-inflammatory, neuroprotective, and antiapoptotic properties (Fu et al, 2018 ; Huang et al, 2019 ; Fan et al, 2021 ). However, due to its poor water solubility, low bioavailability, and difficulty in crossing physiological barriers to reach the injury site, its application in SCI is limited greatly (Zhang et al, 2014 ; Miguel et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The reason that injured CNS would ever produce a neurotoxic reactive astrocyte is still a mystery. Drugs that prevent or revert these subtype of reactive astrocytes may save neurons after spinal cord injury and promote regeneration by stimulating growth and allowing these astrocytes to clear myelin debris (Fan et al, 2021). Oligodendrocytes also display high cell stress levels (Hapln2, Hspa8, and Hsp90ab1), with GO analysis showing many differentially regulated metabolic processes after injury, which indicates that oligodendrocytes transit from a normal to active state.…”
Section: Discussionmentioning
confidence: 99%
“…With substantial advances in the understanding of SCI pathophysiology, it was gradually revealed that the early inflammatory response could also generate a permissive microenvironment for the regeneration of damaged neurons and axons, similar to early inflammatory benefits in other tissues. [57][58][59] Neuroinflammation is composed of multifaceted cellular and molecular responses, and the unique effects of immune cells including macrophages, astrocytes, and lymphocytes are essential for the occurrence and progression of inflammatory responses post-SCI. 60…”
Section: Contribution Of Distinct Immune Cells To Sci Inflammationmentioning
confidence: 99%